Influence of three long-term supplementation systems on dairy cows - Garc?a L?pez, Roberto (Cuban Journal of Agricultural Science, 2010)
One hundred and thirty-five tropical Holstein cows (45 cows/treatment) were spread randomly into three feeding systems: a) supplementation with 0.45 kg of concentrate/L of milk, after the tenth liter of milk produced, B) supplementation with 0.45 kg of concentrate/L of milk, after the fifth liter of milk produced, and C) supplementation with 0.45 kg of concentrate/L of milk up to the tenth week of lactation during three consecutive lactations. The cows had liveweight of 505 ? 27 kg, and remained under study since the first lactation up to the third. The research lasted for four years. The pastures were sampled twice/month, that is, 24 folds/year, for a total of 96 samples throughout the study. Pastures with 24 to 32 d of age were used, depending on the season. The animals were fed Pangola grass (Digitari decumbens Stent), fertilized with 400 kg of N/ha/year. The stocking rate was of 3.5 cows/ha. Irrigation was used during the dry season. In time, milk yield differed between treatments (3667, 3695, 3445 kg for A, B, and C, respectively), whereas the treatment B had the poorest productive milk yield (3.65 kg of milk/kg of concentrate vs 8.7 and 8.5 kg of milk/kg of concentrate in the treatments A and C, respectively). The physiological and productive factors analyzed indicated that the animals with yield lower than 4000 kg/lactation had better indicators when fed concentrate since the tenth liter of milk produced and when the basic pasture surpassed 10 % in protein values, and, also, when there was availability of around 20 kg of DM/d/animal. Key words: feeding system, supplementation, grazing, dairy cows.